2005
DOI: 10.1136/adc.2005.071613
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes services in the UK: fourth national survey; are we meeting NSF standards and NICE guidelines?

Abstract: Background: Previous surveys of children's diabetes service provision in the UK have shown gradual improvements but continuing deficiencies. Aim: To determine whether further improvements in services have occurred. Methods: A questionnaire was mailed to all paediatricians in the UK identified as providing care for children and adolescents with diabetes. Responses were compared with results of three previous surveys, and with recommendations in the Diabetes NSF and the NICE type 1 diabetes guidelines. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…A French study in 2003 of general practitioners caring for diabetic patients reported that only 36% of patients had a urine albumin test and that only a 24-h urine collection was considered adequate (53 ). A survey of British pediatric diabetes care practices reported in 2005 that ACR measurement in morning samples was the predominant test (81%), whereas timed overnight collections and 24-h collections were used by 14% and 5%, respectively (54 ).…”
Section: Urine Sample Collection and Testing Practicesmentioning
confidence: 99%
“…A French study in 2003 of general practitioners caring for diabetic patients reported that only 36% of patients had a urine albumin test and that only a 24-h urine collection was considered adequate (53 ). A survey of British pediatric diabetes care practices reported in 2005 that ACR measurement in morning samples was the predominant test (81%), whereas timed overnight collections and 24-h collections were used by 14% and 5%, respectively (54 ).…”
Section: Urine Sample Collection and Testing Practicesmentioning
confidence: 99%
“…It is essential that regulatory bodies emphasise the need for effective communication underlying high-quality clinical care for children with diabetes. 4,209 These skills need to be learned early on in professionals careers and/or as they enter the field of paediatric diabetes. Evidence for the effectiveness in changing difficult behaviour is provided in MI and SFBT research.…”
Section: Implications For Clinical Servicesmentioning
confidence: 99%
“…2,22,23,[27][28][29][30] From the guidelines and the available evidence it is difficult to define exactly how many patients an individual team should be responsible for, and how many professionals there should be in each team. There is evidence from the UK that children attending larger clinics with more specialised consultants receive better care, 31,32 although a comparison of 207 paediatric diabetes centres in Germany and Austria did not reveal an effect of centre size on HbA1c when comparing centres with less than 50 patients to those with more than 50 patients. 33 Within the UK, the Royal College of Nursing (RCN) recommends a ratio of diabetes specialist nurse to patient of one to no more than 70 children or young people based on their responsibilities and workload.…”
Section: Team Structure and Centre Sizementioning
confidence: 99%
“…65 A recent survey of nursing practice in the UK found that UK ConsensUs ConferenCe on Diabetes S Williamson although numbers of specialist nurses had increased, the mean ratio of nurses to patients was 1:109, 66 well below the recommendation of 1:70, 34 and a survey of services in 2002 in the UK found that most clinics had very limited access to psychology services and inadequate dietetic resources. 32 These findings suggest that without strong incentives or increased financial resources, local health services will not automatically implement these standards in the UK.…”
mentioning
confidence: 99%
See 1 more Smart Citation